Filsafat Ilmu Pandangan Imam Al-Ghazali - Faris Abdurrasyid; Betty Mauli Rosa Bustam; Farid Setiawan; Muhda Ashari Dimiyati Wibawa (Penerbit dan Percetakan CV. Picmotiv, 2024)
Al-Ghazali's thoughts on knowledge are an essential foundation in Islamic philosophy and education. This research aims to comprehensively examine Al-Ghazali's views on the nature, sources, methods, classification, and purpose of knowledge. Through a literature study of Al-Ghazali's works and secondary literature, this research found that Al-Ghazali emphasized the importance of integrating revelation and reason in acquiring knowledge. Al-Ghazali also classified knowledge into various categories, including fardhu 'ain and fardhu kifayah knowledge, as well as theoretical and practical knowledge. This research concludes that Al-Ghazali's thoughts on knowledge are relevant and provide a valuable contribution to the development of contemporary Islamic philosophy of science and education.